THE CORRELATION BETWEEN RELIGIOUS PRACTICE, ACADEMIC PERFORMANCE AND ENGLISH COMPETENCE OF THE ECONOMIC AND BUSINESS FACULTY STUDENTS OF MUHAMMADIYAH UNIVERSITY PALEMBANG - Gumartifa, Asti (English Community Journal, 2018)
English competence is always needed in this globalization era. TOEFL test is always used due to measure students’ ability in understanding English spoken and written. Grade Point Average (GPA) and religious performance practice are suspected whether or not influence students English language competence.  In this paper, religious practice and Grade Point Average (GPA) correlated to English language competence at the economic and business students’ faculty of Muhammadiyah University Palembang. Recent research demonstrated a positive correlation between religious practice and academic performance to English competence. Students’ religiosity was measured using Centrality of Religiosity Scale (CRS) ready-made questionnaire, while academic performance was measured by Grade Point Average (GPA) and TOEFL test was used to determine students’ English language competence. The statistical analysis revealed that there was no significant correlation between students’ religious performance to English language competence. Meanwhile, Grade Point Average showed positive correlation to English language competence.